(untitled) (Jurnal Peternakan Lingkungan Tropis, 2021)
Goats are one of the local domestic small ruminant that have develoment prospects as milk and meat producers and are popular with the community because of the traditional rearing system and good adaptation to an enviroment. The study was aimed to determine the diversity based on the morphometric characteristic of Jawarandu goats in North Samarinda District and to know the characteristics of jawarandu goats in North Samarinda District. The sampling technique was purposive sampling, namaly a specific sampling technique. The determination of the sample goat respondents was carried out with the criteria of goats age 12-24 months, with total samples of 72 heads consisting of 36 buck dan 36 ewe. The data was collected quantitative characteristics including: body wight, body length, shoulder height, and chest circumference of jawarandu goats in North Samarinda. The data was collected analyzed using the Independent T test. The result was showed that there were significant differences in body size in buck and ewe jawarandu goats. Chest circumference with t-count value-1.778< t-table 1.99 with a significant value of 0.019> 0.05, body length t-count value 3.439> t-table 1.99 with a significant value of 0.042>0.05, body weight has no effect with t- count value 0.684< t-table 1.99 with a significant value of 0.000< t-table 1.99 with a significant value of 0.008>0.05. The equation of body size of the jawarandu goat includes body length, shoulder height, chest circumference and the buck goat equation is Y=-30.681+0.985 PB, Y=- 48.032+ 1.191 TP, Y=-62.968+1.381 LD, while the ewe goats Y=-17.226+1.072 PB, Y=-36.34+1.092 TP, Y=-61.85+1.371 LD. The phenotypic characteristics of buck and ewe jawarandu goats obtained varied characteristics of coat color, convex face, and long drooping ears. Morphometrics in male and female jawarandu goats have differences in body size, namely the chest circumference has an average male 72,86±4,80 cm and females 74,53±2,93 cm, the average body length of male is 69,08±6,31 cm and female 64,78±4,06 cm, male average shoulder height 71,53±4,63 cm and female 70,22±3,07 cm, male body weight average 37,17±7,91 kg and female 36,10±4,26 kg.